Development and testing of a rotary type black pepper cleaner - ABDUL WAHAB V. S; Er. Jippu Jacob (Guide) (Tavanur 1995 Kelappaji College of Agricultural Engineering and Technology)
Development and testing of a rotary type black pepper cleaner
Development and testing of a rotary type black pepper cleaner